2015
DOI: 10.1517/14656566.2015.1035646
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mitiglinide and sitagliptin, alone or in combination, on postprandial excursion and glycemic variability assessed by continuous glucose monitoring: apost hocanalysis with single-day treatment

Abstract: Mitiglinide or combination treatment resulted in lower glycemic variability and postprandial glucose excursion than sitagliptin alone; however, the results of this single-day pharmacodynamics study cannot be generalized to a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Based on analysis of the Bland-Altman plot, M-UGCR tended to underestimate overnight 8-hr UGCR. One plausible explanation for this result might be a progressive decline in glucose from midnight to morning, which has been noted in continuous glucose monitoring system (CGMS) device data for Korean type diabetes [202122]. Based on this deduction, a glucose level at the morning fasting time could be lower than the average overnight glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…Based on analysis of the Bland-Altman plot, M-UGCR tended to underestimate overnight 8-hr UGCR. One plausible explanation for this result might be a progressive decline in glucose from midnight to morning, which has been noted in continuous glucose monitoring system (CGMS) device data for Korean type diabetes [202122]. Based on this deduction, a glucose level at the morning fasting time could be lower than the average overnight glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single-day study of 26 type 2 diabetes patients assessed postprandial excursions and glycemic variability with CGM to determine efficacy differences between mitiglinide and sitagliptin, alone or in combination. 35 The 24-h CGM data analysis showed that both mitiglinide and the combination treatment produced lower glycemic variability (24-h glucose variability reflected by mean amplitude of glucose excursion [MAGE], SD, and coefficient of variation [%]; P < 0.001) as well as decreased postprandial glucose excursion (area under the glucose-time curve [AUC], P < 0.001), and a more statistically significant change from baseline in postprandial hyperglycemia than sitagliptin alone (combination P = 0.044; mitiglinide P < 0.001). Moreover, the CGM-measured mean 24-h blood glucose level decreased more significantly in the combination group than in the sitagliptin group (P = 0.009), even when the time spent in the ideal glucose range (70-140 mg/dL) was not significantly improved in any group.…”
Section: Cgm In Clinical Trials Of Glucose-lowering Agentsmentioning
confidence: 99%
“…Against that, while real-time CGM is increasingly used in clinical practice, its use is rejected by some patients on the grounds of cost, frustration over lack of accuracy, alarm and calibration fatigue, or issues of using a technology. 55 Furthermore, even when trial participants were instructed to continue with their usual exercise and diet routine, 35,37,38,41 it cannot be completely discarded that glycemic improvement is not due to CGM-informed decisions on self-management of diabetes, although for the most part, these should affect the test and control arms. It is also possible that CGM-naive people could misinterpret the data to the detriment of their blood glucose control.…”
Section: Maskingmentioning
confidence: 99%